Evaluasi Realisasi Rencana Landuse di Kecamatan Pattallassang, Kabupaten Gowa - Muhammad Reza Prajana; Ihsan Ihsan; Abdul Rachman Rasyid (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2021)
High population growth in a region commonly pushes the government to fast provide public facilities in order to fullfil the public needs. Along with it, one of the challenges that faced by the urban center of Pattallassang Distric in Gowa Regency is rapid land convertion due to high land demand to provide public facilities. This urban area is highly populated and has intense activities because not only it functions as center of government but also as a Special Economic Zone (KEK) of the region. The aim of this research is to evaluate the landuse realization in Gowa Region, between what is found in reality with what has been planned in regional spatial plan (RTRW), as well as to identify the contributing factors behind the discrepancies. This research was conducted from September 2019 to February 2020 (6 months). The data and information were collected through literature study related to land suitability evaluation methods, influencing factors, and field survey. The research used method of spatial analysis using overlay techniques with the help of software ArcGIS 10.1, scoring analysis to define the suitability value, and qualitative descriptive analysis to determine factors that contribute to the discrepancy between existing landuse and the RTRW document. The results showed that among the many landuse discrepancies, the residential landuse has the lowest value of suitability value of 24%. Economical and environmental factors may play important roles in this discrepancy.